2015
DOI: 10.1103/physreva.92.033612
|View full text |Cite
|
Sign up to set email alerts
|

Impurity in a Bose-Einstein condensate: Study of the attractive and repulsive branch using quantum Monte Carlo methods

Abstract: We investigate the properties of an impurity immersed in a dilute Bose gas at zero temperature using quantum Monte Carlo methods. The interactions between bosons are modeled by a hard-sphere potential with scattering length a, whereas the interactions between the impurity and the bosons are modeled by a short-range, square-well potential where both the sign and the strength of the scattering length b can be varied by adjusting the well depth. We characterize the attractive and the repulsive polaron branch by c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
216
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(237 citation statements)
references
References 42 publications
18
216
3
Order By: Relevance
“…We report measurements of the Bose polaron energies and lifetimes using RF spectroscopy of fermionic 40 K impurities in a BEC of 87 Rb atoms. We tune the impurityboson interactions using a Feshbach resonance, and our measurements reveal both an attractive and a repulsive polaron branch, whose energies agree with recent predictions [11][12][13]. We find that the Bose polaron exists across the strongly interacting regime and has a larger binding energy than does the low-density, two-body molecular state.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…We report measurements of the Bose polaron energies and lifetimes using RF spectroscopy of fermionic 40 K impurities in a BEC of 87 Rb atoms. We tune the impurityboson interactions using a Feshbach resonance, and our measurements reveal both an attractive and a repulsive polaron branch, whose energies agree with recent predictions [11][12][13]. We find that the Bose polaron exists across the strongly interacting regime and has a larger binding energy than does the low-density, two-body molecular state.…”
supporting
confidence: 62%
“…Impurity atoms immersed in a degenerate bosonic or fermionic atomic gas are a convenient experimental realization for Bose or Fermi polaron physics, respectively. Recent theoretical work [2][3][4][5][6][7][8][9] has explored the Bose polaron case, and the ability to use a Feshbach resonance to tune [10] the impurity-boson scattering length a IB opens the possibility of exploring the Bose polaron in the strongly interacting regime [11][12][13][14]. Experiments to date [15][16][17][18][19][20] have focused on the weak Bose polaron limit.…”
mentioning
confidence: 99%
“…As the limiting case of a many-body system in the large polarization limit, mobile impurity and its associated quasi-particle excitations contain valuable information of the underlying system. Whereas impurity problems in the background of Bose gases or Fermi condensates have attracted considerable attention in recent years [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63], here we focus on the case of an impurity against a non-interacting Fermi sea. In alkali atoms, it has been shown that the impurity can either form a tightly bound molecule with a majority atom, or induce collective particle-hole excitations in the Fermi sea arXiv:1710.05166v1 [cond-mat.quant-gas] 14 Oct 2017…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a great attention of theorists [1][2][3][4][5][6][7][8][9][10][11] has been paid to the analysis of a mobile impurity properties in the Bose gas. Such a renascence of the old problem well-studied in the context of a single 3 He atom immersed in liquid 4 He (see, for instance [13][14][15][16], and references there) is stimulated by the success of the experimental techniques [17,18] where the possibility to control a small amount of impurity particles strongly coupled to the bosonic bath is demonstrated.…”
Section: Introductionmentioning
confidence: 99%